The Suppressed Induction of Human Mature Cytotoxic T Lymphocytes Caused by Asbestos Is Not due to Interleukin-2 Insufficiency - Naoko Kumagai-Takei; Yasumitsu Nishimura; Hidenori Matsuzaki; Suni Lee; Kei Yoshitome; Hiroaki Hayashi; Takemi Otsuki (Journal of Immunology Research)
We previously reported that exposure to chrysotile B (CB) asbestos suppressed the induction of mature cytotoxic T lymphocytes (CTLs) during mixed lymphocyte reaction assays (MLRs) with a decrease in the proliferation of immature CTLs. However, the mechanism responsible for the effect of asbestos fibers on the differentiation of CTLs remains unclear. Since interleukin-2 (IL-2) is a regulator of T lymphocyte proliferation, we examined the effect of IL-2 addition on suppressed CTL differentiation in CB-exposed cultures using flow cytometry (FCM). When IL-2 was added at 1 ng/mL on the second day of MLRs, the asbestos-caused decreases in the proliferation and percentages of CD25+ and CD45RO+ cells in CD8+ lymphocytes were not recovered by IL-2 addition, although the decrease in percentage of granzyme B+ cells was partially recovered. CD8+ lymphocytes from the IL-2-treated culture with asbestos showed the same degree of cytotoxicity as those in cultures without IL-2 or asbestos. These findings indicate that IL-2 insufficiency is not the main cause for the suppressed induction of CTLs by asbestos exposure, although they suggest a potential for the improvement of such suppressed CTL functions. Secretory factors other than IL-2 in addition to membrane-bound stimulatory molecules may play a role in asbestos-caused suppressed CTL differentiation.